Understanding the Dynamics of Gender and Nutrition in Bangladesh : Implications for Policy and Programming - World Bank (Washington, DC, 2013)
During the past two decades, Bangladesh has made considerable progress in development, sustaining high rates of economic growth and reducing poverty rates by nine percent between 2000 and 2005. This report aims to contribute to reducing malnutrition in Bangladesh through a better understanding of gender-nutrition linkages. It is also part of a larger effort on multisectoral approaches to improving nutrition. The report takes as its starting point, the hypothesis that gender inequality in Bangladesh is instrumental in shaping nutrition outcomes. This study has demonstrated that gender and nutrition are intimately associated and that there are strong linkages between women's status and both their own, and their children's nutritional status.